Analysis of UK precipitation extremes derived from Met Office gridded data. (6th November 2013) - Simpson, I. R.; Jones, P. D.
ABSTRACT In Simpson and Jones (2012) we introduced new, homogenized UK national and regional rainfall series derived from 5 km gridded daily and monthly precipitation data. The monthly series were extended back to 1766 for monthly England and Wales (EW) precipitation, to 1873 for monthly values for each of the five EW sub‐regions, and to 1931 for daily values in all regions. Using data from those series, this paper provides analysis of how mean precipitation totals and extremes have changed over the respective periods. The results showed statistically significant upward trends in mean and extreme winter, spring and autumn precipitation for some Scottish regions, but trends over England and Wales were mostly insignificant, though England and Wales had a significant increase in winter precipitation over 1766–2011. The trend in summer precipitation over 1931–2011 has been statistically insignificant, though with a significant long‐term downward trend for England and Wales over 1766–2011. Prior observations of a trend towards drier summers and wetter winters have been complicated by a recent succession of wet summers and dry winters. Many of the observed changes in seasonal precipitation totals are most likely associated with changes in the North Atlantic Oscillation.